Comparative efficacy and safety of Chinese medicine injections as an adjunctive therapy for cervical cancer in Chinese patients: a network meta-analysis - Fei Ma; Qun Wang; Di Zhang; Zihong Wang; Hui Xie; Xianghong Liu; Hongxing Zhang; Haiyan Song; Shiguang Sun (Pharmaceutical Biology)
Context Chinese medicine injections (CMIs) are widely used as adjuvant therapy for cervical cancer in China. However, the effectiveness of different types of CMIs remains uncertain.Objective To assess the effectiveness and safety of CMIs when used in conjunction with radiotherapy (RT) or concurrent chemoradiotherapy (CCRT), particularly in combination with cisplatin (DDP), docetaxel plus cisplatin (DP), and paclitaxel plus cisplatin (TP).Materials and methods Randomized controlled trials (RCTs) were searched in databases including CNKI, WanFang, VIP, SinoMed, PubMed, Cochrane Library, Embase, and Web of Science from inception to September 2023. We calculated the risk ratio with a 95% confidence interval and the surface under the cumulative ranking area curve (SUCRA) for the clinical efficacy rate (CER), the efficacy rate by Karnofsky Performance Status (KPS), and the rates of leukopenia reduction (LRR) and gastrointestinal reactions (GRR).Results Forty-seven RCTs were included, including nine CMI types: Aidi, Fufangkushen, Huangqi, Kangai (KA), Kanglaite (KLT), Renshenduotang, Shenqifuzheng (SQFZ), Shenmai (SM), and Yadanzi. KLT and KA were likely optimal choices with radiotherapy for CER and KPS, respectively. KA and KLT were optimal choices with RT + DDP for CER and GRR, respectively. KLT was the likely optimal choice with RT + DP for CER and KA for both KPS and GRR. SM and SQFZ were the likely optimal choices with RT + TP for CER and LRR, respectively.Conclusions The optimal recommendation depends on whether CMIs are used with radiotherapy or concurrent chemoradiotherapy. More high-quality RCTs are needed to confirm further and update the existing evidence.